Assessment of erosion and settling properties of fine sediments stored in cobble bed rivers: the Arc and Isère alpine rivers before and after reservoir flushing. Issue 6 (19th January 2018) - Legout, C.; Droppo, I.G.; Coutaz, J.; Bel, C.; Jodeau, M.
Abstract: Cohesive sediment dynamics in mountainous rivers is poorly understood even though these rivers are the main providers of fine particles to the oceans. Complex interactions exist between the coarse matrix of cobble bed rivers and fine sediments. Given that fine sediment load in such environments can be very high due to intense natural rainfall or snowmelt events and to man‐induced reservoir or dam flushing, a better understanding of the deposition and sedimentation processes is needed in order to reduce ecohydrological downstream impacts. We tested a field‐based approach on the Arc and Isère alpine rivers combining measurements of erosion and settling properties of river bed deposits before and after a dam flushing, with the U‐GEMS (Gust Erosion Microcosm System) and SCAF (System Characterizing Aggregates and Flocs), respectively. These measurements highlight that critical shears, rates of erosion, settling velocities and propensity of particles to flocculate are highly variable in time and space. This is reflective of the heterogeneity of the hydrodynamic conditions during particle settling, local bed roughness, and nature and size of particles. Generally the deposits were found to be stable relative to what is measured in lowland rivers. It was, however, not possible to make a conclusive assessment of the extent to which the dynamics of deposits after reservoir flushing were different from those settled after natural events. The absence of any relationships between erosion and deposition variables, making it impossible to predict one from another, underlined the need to measure all of them to have a full assessment of the fine sediment dynamics and to obtain representative input variables for numerical models. While the SCAF was found to be effective, an alternative to the U‐GEMS device will have to be found for the erodibility assessment in cobble bed rivers, in order to make more rapid measurements at higher shears. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : The combined use of the U‐GEMS (Gust Erosion Microcosm System) and SCAF (System Characterizing Aggregates and Flocs) devices to characterize river bed fine deposits showed that the critical shears, rates of erosion, settling velocities and propensities of particles to flocculate are highly variable in time and space. The absence of any relationships between the measured variables, making it impossible to predict one from another, underlined the need to measure all of them to have a full assessment of fine sediment dynamics.